2013
DOI: 10.1126/scisignal.2004214
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor CREB Enhances Interleukin-17A Production and Inflammation in a Mouse Model of Atherosclerosis

Abstract: It has been demonstrated that 15-lipoxygenase (15-LO) plays a role in atherogenesis, but the underlying mechanisms were unclear. Therefore, the purpose of the present study is to explore the mechanisms of 15-LO role in atherogenesis. 15(S)-hydroxyeicosatetraenoic acid [15(S)-HETE], the major 15-LO-dependent metabolite of arachidonic acid (AA), stimulated the production of reactive oxygen species (ROS) by monocytes through the xanthine oxidase–mediated activation of NADPH oxidase, which led to the Syk-, Pyk2-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 58 publications
1
62
0
Order By: Relevance
“…We also found that 15(S)-HETE increases XO activity in macrophages ( 22 ). These observations led us to hypothesize that XO might be involved in 15(S)-HETE-induced EC barrier dysfunction.…”
Section: Mass Spectroscopymentioning
confidence: 62%
“…We also found that 15(S)-HETE increases XO activity in macrophages ( 22 ). These observations led us to hypothesize that XO might be involved in 15(S)-HETE-induced EC barrier dysfunction.…”
Section: Mass Spectroscopymentioning
confidence: 62%
“…We have previously shown that 15(S)-HETE by activating nonreceptor tyrosine kinases, Src and Pyk2, stimulates ZO-2 tyrosine phosphorylation and its dissociation from claudins 1/5 and thereby disrupts aortic endothelial TJs in response to HFD feeding (27). We have also shown that 15(S)-HETE induces reactive oxygen species production via xanthine oxidase and an NADPH oxidase-dependent manner in macrophages (63). Furthermore, our studies have demonstrated that the macrophages from apoE Ϫ/Ϫ :12/15-LO Ϫ/Ϫ mice exhibited lower capacity in the production of oxidants as compared with apoE Ϫ/Ϫ mice in response to HFD feeding (63).…”
Section: Discussionmentioning
confidence: 80%
“…We have also shown that 15(S)-HETE induces reactive oxygen species production via xanthine oxidase and an NADPH oxidase-dependent manner in macrophages (63). Furthermore, our studies have demonstrated that the macrophages from apoE Ϫ/Ϫ :12/15-LO Ϫ/Ϫ mice exhibited lower capacity in the production of oxidants as compared with apoE Ϫ/Ϫ mice in response to HFD feeding (63). In view of these findings and the present observations, it may be suggested that 15-LO1/15(S)-HETE axis (12/15-LO/12(S)-HETE axis in mice), via triggering both tyrosine and serine/threonine phosphorylation of various endothelial TJ proteins and thereby disrupting endothelial TJs, increasing vascular permeability, and enhancing vascular inflammation, might be playing a contributing role in atherogenesis in response to cardiovascular risk factors such as HFD.…”
Section: Discussionmentioning
confidence: 97%
“…The Murine Homologue of 15-LOX-2 Is an 8-LOX-15-S-HETE (generated by non-enzymatic reduction of 15-S-HPETE) has been shown to be the LOX product that contributes to atherosclerosis in a murine model system (9). However, silencing expression of murine ALOX15B (which produces 8-HPETE from AA rather than 15-HPETE) mitigated plaque formation (8).…”
Section: -Lox-2 and 5-lox Differ In The Orientations Of Theirmentioning
confidence: 99%
“…More recently, Magnusson et al (8) demonstrated that silencing production of the ALOX15B protein in human macrophages decreased cellular lipid accumulation, the precipitating factor in foam cell formation. Finally, 15S-hydroxyeicosatetraenoic acid (HETE), derived through non-enzymatic reduction of the product of the 15-LOX reaction, has been shown to promote formation of atherosclerotic lesions in a mouse model system (9).…”
mentioning
confidence: 99%